Pelaksanaan Pendaftaran Peralihan Hak Atas Tanah Karena Jual Beli - nuridin, nuridin; Wildan, Muhammad; Pratama, Erwin Aditya (Universitas Pancasakti Tegal, 2020)
Buying and selling is something that is already familiar to us. Buying and selling in this case the sale and purchase of land rights often occurs in the community, but in its implementation the community has not been too understanding in terms of land registration procedures due to legal acts of sale and purchase. The lack of understanding from the community resulted in disputes in the future such as the rise of disputes over land rights resulting from the transfer of rights to land that had not yet been registered. This writing uses a normative juridical research method, where this study refers to the provisions of applicable laws and regulations. The results of the study show that legal actions through buying and selling must be officially registered with the local Land Office. The purpose of registering the transfer of land rights is to obtain legal guarantees for the parties regarding ownership of the land rights. So that there is a need for further understanding of the importance of registration of land rights due to buying and selling.